Ca2+-sensors and ROS-GC: interlocked sensory transduction elements: a review - Sharma, Rameshwar K.; Duda, Teresa (Frontiers in Molecular Neuroscience, 2012)
From its initial discovery that ROS-GC membrane guanylate cyclase is a mono-modal Ca2+-transduction system linked exclusively with the phototransduction machinery to the successive finding that it embodies a remarkable bimodal Ca2+signaling device, its widened transduction role in the general signaling mechanisms of the sensory neuron cells was envisioned. A theoretical concept was proposed where Ca2+-modulates ROS-GC through its generated cyclic GMP via a nearby cyclic nucleotide gated channel and creates a hyper- or depolarized sate in the neuron membrane (Ca2+ Binding Proteins 1:1, 7-11, 2006). The generated electric potential then becomes a mode of transmission of the parent [Ca2+]i signal. Ca2+ and ROS-GC are interlocked messengers in multiple sensory transduction mechanisms. This comprehensive review discusses the developmental stages to the present status of this concept and demonstrates how neuronal Ca2+-sensor proteins are the interconnected elements of this elegant ROS-GC transduction system. The focus is on the dynamism of the structural composition of this system, and how it accommodates selectivity and elasticity for the Ca2+ signals to perform multiple tasks linked with the SENSES of vision, smell and possibly of taste and the pineal gland. An intriguing illustration is provided for the Ca2+ sensor GCAP1 which displays its remarkable ability for its flexibility in function from being a photoreceptor sensor to an odorant receptor sensor. In doing so it reverses its function from an inhibitor of ROS-GC to the stimulator of ONE-GC membrane guanylate cyclase.